2012
DOI: 10.1080/00103624.2012.684987
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Traits of Corn Fertilized with Sewage Sludge

Abstract: Although research on the environmental impacts of using waste as a fertilizer is of great importance, the basic principle for using a product as fertilizer is that it should provide nutrients for plants without causing any harm to them. The objective of this study was to evaluate the agronomic traits (number of nodes, plant height, leaf number, yield, and protein content of grains) and the nutritional status of corn treated with sewage sludge. The experiment was conducted in the municipality of Jaboticabal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…This indicates that SS is efficient in providing P to the plants (Lee et al, 2018) without the need for mineral fertilizer supplementation (Tontti et al, 2017). In other years, in the same experiment, similar results were observed for other crops (Ribeirinho et al, 2012;Macedo et al, 2012) in relation to P uptake.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This indicates that SS is efficient in providing P to the plants (Lee et al, 2018) without the need for mineral fertilizer supplementation (Tontti et al, 2017). In other years, in the same experiment, similar results were observed for other crops (Ribeirinho et al, 2012;Macedo et al, 2012) in relation to P uptake.…”
Section: Discussionsupporting
confidence: 80%
“…The treatments that received SS needed to be supplemented with N from the mineral fertilizer, since not all the N contained in SS is bioavailable. However, our results showed that the N application from mineral fertilizers can be partially replaced by SS and reach large yields (Macedo et al, 2012;Motta and Maggiore, 2013;Yagmur et al, 2017). Our study also showed that even with the large imbalance between the amount of micronutrients contained in SS and the amount required by maize plants, SS proved to be efficient in providing micronutrients to maize plants (Pigozzo et al, 2000;Macedo et al, 2014;Nikzad et al, 2015).…”
Section: Discussionmentioning
confidence: 64%
“…Мутации KRAS и NRAS в целом сильно различаются между спорадическими поражениями КРР, и статус этих мутаций в метастазах опухоли непредсказуем [13].…”
Section: онкология и радиология казахстана №2 (68) 2023unclassified
“…Жидкостная биопсия может быть использована для обнаружения мутаций KRAS во вкДНК в случаях, когда мутация не была определена при биопсии первичной опухоли. Это может быть основополагающим шагом выбора терапии, поскольку опухолевые клетки с мутаци-KRAS устойчивы к лечению моноклональными антителами против EGFR [13]. Для достижения эффективного клинического использования жидкостной биопсии предстоит выполнить важную работу по стандартизации как преаналитических, так и аналитических процедур и обобщить их для всех компонентов жидкостной биопсии.…”
Section: онкология и радиология казахстана №2 (68) 2023unclassified
“…Mays and Giordano (1988), determined a decline in maize yield but metal concentrations did not exceed threshold values in soil depending on sludge application. Macedo et al (2012), studied the effects of sludge on yield and quality parameters of wheat and suggested that sludge can be a value nutrient source. Junio et al (2011), two doses of rock phosphate (0 and 90 kg P 2 O 5 ha -1 ) and four doses of sewage sludge compost (0, 25, 50 and 75 MT ha -1 ) were applied to soil and evaluated the concentration of heavy metals in soil and leaves of maize fertilized with rock phosphate and sewage sludge compost.…”
Section: Introductionmentioning
confidence: 99%